Reflection of Customer Experience and Destination Image of Tourist Trust through Satisfaction Mediation - Ika Barokah Suryaningsih; Kristian Suhartadi Widi Nugraha; Arnas Yulio Sukmalangga (Faculty of Economics and Business, Hasanuddin University, Makassar, Indonesia, 2020)
In the tourism services sector, tourist experience and destination image are the keys to create tourist satisfaction. Thus, tourists are expected to gain pleasure and lead to a build of tourist' trust in the beach destination. Research objectives are to prove the effect of customer experience and destination image on trust through the mediation of tourist satisfaction. The population were all tourists who had visited a beach in Trenggalek Regency more than two times. The sampling technique used was accidental sampling with 193 respondents. Data collection was carried out by a questionnaire containing statement items which were given a score of 1-5 using a Likert scale, and the analysis tool was use PLS. The results imply that customer experience and destination image affect tourist satisfaction. Tourist experience was not significant on trust, but destination image influences trust of the tourist.On the other hand, tourist satisfaction affects tourist' trust. This research proves that the more satisfied tourists, it would be to increase tourist’ trust. The Sobel test shows that the intervening variable, namely tourist satisfaction, can mediate the influence of the variable of tourist experience and destination image on trust when visiting the beach